Spin state switching in iron coordination compounds - Gütlich, Philipp; Gaspar, Ana B.; Garcia, Yann (Beilstein Journal of Organic Chemistry, 2013)
The article deals with coordination compounds of iron(II) that may exhibit thermally induced spin transition, known as spin crossover, depending on the nature of the coordinating ligand sphere. Spin transition in such compounds also occurs under pressure and irradiation with light. The spin states involved have different magnetic and optical properties suitable for their detection and characterization. Spin crossover compounds, though known for more than eight decades, have become most attractive in recent years and are extensively studied by chemists and physicists. The switching properties make such materials potential candidates for practical applications in thermal and pressure sensors as well as optical devices.The article begins with a brief description of the principle of molecular spin state switching using simple concepts of ligand field theory. Conditions to be fulfilled in order to observe spin crossover will be explained and general remarks regarding the chemical nature that is important for the occurrence of spin crossover will be made. A subsequent section describes the molecular consequences of spin crossover and the variety of physical techniques usually applied for their characterization. The effects of light irradiation (LIESST) and application of pressure are subjects of two separate sections. The major part of this account concentrates on selected spin crossover compounds of iron(II), with particular emphasis on the chemical and physical influences on the spin crossover behavior. The vast variety of compounds exhibiting this fascinating switching phenomenon encompasses mono-, oligo- and polynuclear iron(II) complexes and cages, polymeric 1D, 2D and 3D systems, nanomaterials, and polyfunctional materials that combine spin crossover with another physical or chemical property.
Keywords: cages; iron(II) coordination compounds; physical techniques; polyfunctional materials; spin crossover